The Thirunangai Promise: Gender as a contingent outcome of migration and economic exchange - Nataraj, Shakthi (Anti-Trafficking Review, 2022)
In this paper, I track how social actors in the city of Chennai in the Indian state of Tamil Nadu contested the boundaries of thirunangai identity, the preferred Tamil term for transgender women. Using a framework derived from linguistic and economic anthropology, I show how gendered personhood is a contingent outcome of the value and meaning given to migrations and economic exchanges, where migration makes new gendered subjectivities possible while curtailing others. I offer a queer analysis of migration, highlighting how social womanhood is a contingent achievement and a contested status, split along axes of class, caste, religion, language, cis- or transgenderhood, and so forth. Not all persons socially categorised as women marry, migrate or labour in the same way, and gender is never a singular or isolated axis of differentiation.